The President’s dilemma: the Portuguese semi- presidential system in times of crisis (2011–16) - Freire, A.; Santana Pereira, J. (International Journal of Iberian Studies, 2019)
Economic crises and foreign interventions cause political actors to face a dilemma between responsiveness towards their electorate and responsibility vis-à-vis international institutions. In this article, we analyse how a seldom studied political actor in international affairs (the Head of State in a semi-presidential regime) dealt with this dilemma. We focus on Aníbal Cavaco Silva’s (former president of the Portuguese Republic) discourse, and use of veto and constitutionality examination request powers in the 2011–16 mandate, and on his attitudes regarding the access to power of pro- and anti-austerity political forces in the aftermath of legislative elections. We conclude that the Head of State was more concerned with international responsibility than with domestic responsibility and responsiveness, especially at the behavioural level, although he occasionally acted in ways that toned down this feature of his presidential mandate. We therefore suggest that in times of severe crisis the political conditions that usually partly explain variations in the use of the presidential powers in semi-presidential regimes interact with short-term factors related to the crisis that can reduce or even cancel out their effects.